Regulation of CRAC channels and agonist-induced Ca2+ signals - Douglas, S (2012)
Calcium ions (Ca2+) are extremely important intracellular messengers, activating a plethora of cellular processes. Growing evidence now points to a major role for the local Ca2+ signal in driving specific cellular responses. The simplest and most fundamental local Ca2+ signal is the Ca2+ microdomain, which rapidly forms when Ca2+ permeable ion channels open. In non-excitable cells the dominant Ca2+ entry channels are store-operated Ca2+ channels (SOCCs). The best characterised is the Ca2+ release activated Ca2+ (CRAC) channel. How local Ca2+ entry through CRAC channels impacts on channel function however is unclear. I have investigated the interaction between the Ca2+ binding protein calmodulin and CRAC channel activity and subsequent agonist-induced Ca2+ signals. Furthermore, I have investigated a role for mitofusin 2 (a protein that is known to tether the ER and mitochondria) on these Ca2+ signals. Using three different calmodulin mutant constructs with alterations to their Ca2+ binding sensitivities, I have shown that calmodulin facilitates CRAC channel dependent Ca2+ entry and maintains agonist-induced cytosolic Ca2+ oscillations in a lobe-specific manner. Calmodulin has four Ca2+ binding sites, two on the N-lobe and two on the C-lobe. I found a dominant negative calmodulin mutant (CAM4M, where all four binding sites had been mutated), or one where the C-lobe could not bind Ca2+ (CAM2C), impaired both Ca2+ influx through CRAC channels and maintenance of cytosolic Ca2+ oscillations. In contrast, a Ca2+-insensitive N-lobe mutant had little effect, (CAM2N). Knockdown of the mitochondrial Ca2+ uniporter regulator (MICU1) or mitochondrial membrane depolarization had similar effects to those seen with CAM4M or CAM2C, suggesting that at least in part, the action of calmodulin was through regulation of mitochondrial Ca2+ dynamics. This was confirmed by directly measuring the mitochondrial matrix Ca2+ concentration in intact RBL-1 cells using the mitochondrial targeted, fluorescent protein, pericam. Both CAM4M and disruption of mitochondrial Ca2+ buffering impaired agonist-induced mitochondrial Ca2+ uptake, suggesting that the modulation of CRAC channels occurred through Ca2+-calmodulin facilitation of mitochondrial Ca2+ uptake. Using a mutant Orai1 (A73E) that cannot bind calmodulin, I have shown that calmodulin tethered to the CRAC channel provides a major source of calmodulin for effective mitochondrial Ca2+ uptake. Physiological relevance of my proposed pathway was provided from experiments where I showed knockdown of MICU1 impaired agonist-induced CRAC channel dependent NFAT-1-driven gene expression. In addition, I establish a crucial role for mitochondrial MFN2 and presumably its ability to properly link the mitochondria and ER in the control of CRAC channels and agonist-induced Ca2+ signals.